2018
DOI: 10.1089/dna.2017.3962
|View full text |Cite
|
Sign up to set email alerts
|

APTM, a Thiophene Heterocyclic Compound, Inhibits Human Colon Cancer HCT116 Cell Proliferation Through p53-Dependent Induction of Apoptosis

Abstract: To evaluate the in vitro anticancer activity and to investigate the mechanism of action of a thiophene heterocyclic compound, [3-Amino-5-[(2,6-dimethylphenyl)amino]-4-(phenylsulfonyl)-2-thienyl](4-fluorophenyl)methanone (APTM) against human colon cancer HCT116 cells. Sulforhodamine B assay and colony formation assay for cell proliferation assay; propidium iodide (PI) staining for cell cycle profile analysis; Hoechst staining; annexin V-FITC/PI double staining and Western blotting for apoptosis assay. APTM inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…KEGG enrichment analysis of DEGs in cell transcriptome sequencing showed that FCN3 upregulation was associated with the p53 signaling pathway (Fig. 2B), which was widely reported to be involved in cell proliferation, apoptosis (20)(21)(22). Meanwhile, Gene set enrichment analysis (GSEA) was performed with TCGA data and the results indicated that the high expression of FCN3 was closely related to apoptosis (Fig.…”
Section: Fcn3 Overexpression Promoted Apoptosis and Suppressed Prolif...mentioning
confidence: 95%
“…KEGG enrichment analysis of DEGs in cell transcriptome sequencing showed that FCN3 upregulation was associated with the p53 signaling pathway (Fig. 2B), which was widely reported to be involved in cell proliferation, apoptosis (20)(21)(22). Meanwhile, Gene set enrichment analysis (GSEA) was performed with TCGA data and the results indicated that the high expression of FCN3 was closely related to apoptosis (Fig.…”
Section: Fcn3 Overexpression Promoted Apoptosis and Suppressed Prolif...mentioning
confidence: 95%
“… 32 The oligomerization of these proteins on the mitochondrial outer membrane increases its permeability and triggers the discharge of apoptosis-inducing mediators such as cytochrome C, Smac, and other proteins that promote caspase activity to kill the cell through the intrinsic apoptotic pathway. 33 , 34 …”
Section: Resultsmentioning
confidence: 99%
“…32 The oligomerization of these proteins on the mitochondrial outer membrane increases its permeability and triggers the discharge of apoptosisinducing mediators such as cytochrome C, Smac, and other proteins that promote caspase activity to kill the cell through the intrinsic apoptotic pathway. 33,34 In an attempt to understand the molecular mechanism underlying the anticancer activity of compound 1, the expression of Bax, Bcl-2, and p53 was examined by Western blotting in HCT-116 cells that were more sensitive to compound 1 compared to MCF-7 cells as inferred from the MTT cell viability assay. HCT-116 cells were subjected to various doses of compound 1 for 48 hours and results are shown in Fig.…”
Section: Western Blot Analysismentioning
confidence: 99%